A low alloy high toughness ultra-high strength steel
By adjusting the chemical composition and heat treatment process, the microstructure of lath martensite + residual austenite + fine spherical carbides is formed, which solves the problem of high cost of existing ultra-high strength steels and achieves the balanced effect of low cost, high toughness and ultra-high strength.
Patent Information
- Application Number
- CN202310120453.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-02-14
Smart Images

Figure CN116287982B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of low alloy steel, in particular to a low alloy high toughness ultra-high strength steel. Compared with AerMet100 steel and the like, the Ni content is reduced exponentially and Co is not used. Compared with A1SI4340 steel or D6AC steel and the like, the situation that the C content is too high and the Ni content is too low at the same time is adjusted, so as to better take into account the balanced effect of low cost, high toughness and ultra-high strength. The high toughness and ultra-high strength refer to the following test results according to national standards GB / T 228.1-2018 and GB / T229-2007: tensile strength ≥1950MPa, yield strength ≥1500MPa, elongation ≥10.0%, area reduction ≥40%, and impact energy ≥60J. Background Art
[0002] Ultra-high strength steel generally refers to alloy steel with a tensile strength exceeding 1400MPa and a yield strength exceeding 1300MPa. In addition to requiring ultra-high strength, it is also required to have sufficient toughness, fatigue resistance, and other requirements such as corrosion resistance and creep resistance according to service conditions. It is widely used in aircraft landing gear, high-strength bolts, bulletproof steel plates, rocket engine casings, high-pressure vessels, automotive key components, firearms components, penetrating bullet casings, etc. With the development of high-tech and the need to save resources, ultra-high strength steel is required to have both high strength and toughness and low cost.
[0003] At present, steels with ultra-high strength and toughness, such as AerMet100 (Ni=11-12%, Co=13-14%), 9Ni-5Co, AF1410 (Ni=9.5-10.5%, Co=13.5-14.5%), 18Ni(250), G99 (Ni=9.68%, Co=9.94%), etc., have a large amount of Co and Ni added. Co can promote the fine and dispersed distribution of precipitation phase particles by affecting the dislocation substructure, achieving a significant precipitation strengthening effect to improve the strength and toughness of steel, and Ni can improve the matrix layer of carbon steel. Dislocation energy makes it easier for screw dislocations to cross-slip and improves the toughness of steel. However, Co and Ni are both scarce strategic resources in my country, which makes them very expensive and difficult to be widely used. Low-cost ultra-high strength steel A1SI4340 (where C = 0.38-0.43%, Ni = 1.65-2.0%), 300M (where C = 0.41-0.46%, Ni = 1.6-2.0%), D6AC (where C = 0.38-0.43%, Ni = 1.65-2.0%) has a high C content and a low Ni content. After quenching, the strength is very high but the plastic toughness is very poor. Therefore, from the perspective of saving resources and improving the overall quality of domestic ultra-high strength and toughness steel, it is very necessary to develop an ultra-high strength steel with a low alloy content and excellent strength and toughness. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a low-alloy, high-toughness, ultra-high-strength steel. Compared with AerMet100 steel and the like, the Ni content is reduced exponentially and Co is not used. Compared with A1SI4340 steel or D6AC steel and the like, the situation in which the C content is too high and the Ni content is too low is adjusted, thereby better taking into account the balanced effect of low cost, high toughness and ultra-high strength. The ultra-high strength and high toughness refer to the following test results according to the national standards GB / T 228.1-2018 and GB / T229-2007: tensile strength ≥1950MPa, yield strength ≥1500MPa, elongation ≥10.0%, area reduction ≥40%, and impact energy ≥60J.
[0005] The technical solution of the present invention is as follows:
[0006] A low-alloy high-toughness ultra-high strength steel, characterized in that it includes the following chemical elements and their wt% content: C=0.22-0.38, Si=1.10-2.20, Mn=0.80-2.20, Cr=0.70-1.20, Ni=2.25-4.50, Mo=0.50-1.35, V=0.09-0.35, Nb=0.01-0.04, S≤0.0015, P≤0.005, Fe=balance.
[0007] The ultra-high strength and high toughness refer to the following test results in accordance with national standards GB / T 228.1-2018 and GB / T229-2007: tensile strength ≥1950MPa, yield strength ≥1500MPa, elongation ≥10.0%, area reduction ≥40%, and impact energy ≥60J.
[0008] After the low alloy high toughness ultra-high strength steel is subjected to the heat treatment process of quenching + tempering, its metallographic structure can be seen as lath martensite + residual austenite + fine spherical carbides under an optical microscope magnified 500 times, and the original austenite grain size is relatively small. The metallographic structure is as shown in the figure of the specification. Figure 1 .
[0009] After the low alloy high toughness ultra-high strength steel is subjected to the quenching + tempering heat treatment process, its microstructure can be seen under a scanning electron microscope magnified 10000 times that fine spherical carbides are dispersed in the lath martensite matrix. The microstructure is as shown in the accompanying drawings of the specification. Figure 2 .
[0010] The quenching + tempering heat treatment process is as follows: 1050°C × 1h + oil-cooling quenching, and 260°C × 2h + air-cooling tempering. The chemical element composition and wt% content of the low-alloy high-toughness ultra-high strength steel are as follows: C = 0.24, Si = 1.18, Mn = 1.12, Cr = 0.95, Ni = 2.35, Mo = 1.08, V = 0.11, Nb = 0.028, S ≤ 0.0015, P ≤ 0.005, Fe = balance.
[0011] The low alloy high toughness ultra-high strength steel undergoes a smelting process, a forging process, and a post-forging annealing process in sequence from front to back before undergoing a quenching+tempering heat treatment process.
[0012] The smelting process includes smelting in a vacuum induction furnace or smelting in an electric arc furnace + refining outside the furnace, followed by vacuum consumable remelting or electroslag remelting; the forging process is to perform three-upsetting and three-drawing on the smelted steel ingot, specifically including the following steps: step 1, the initial forging temperature is 1080±10°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; step 2, heating to 1080±10°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; step 3, heating to 1080±10°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height. 10℃, upset to 1 / 2 of the original height, and then forged or rolled into bars or square billets of corresponding sizes according to product requirements. The final forging temperature of the above steps is ≥860℃; the post-forging annealing process includes: heating the forging to 640-660℃ and keeping it for 10h, then furnace cooling to 250-280℃ and keeping it for 10h, then heating to 880℃ and keeping it for ≥12h, air cooling to 250-280℃ and keeping it for 10h, finally heating to 665℃ and keeping it for ≥20h, cooling to 150℃ with the furnace and air cooling out of the furnace.
[0013] The technical effects of the present invention are as follows: the present invention discloses a low-alloy high-toughness ultra-high strength steel, which is alloyed by adding Cr, Mo, Ni, V and Nb, wherein Cr and Mo can play the role of solid solution strengthening and alloy carbide strengthening; Ni can form a film-like austenite between martensite laths, and make screw dislocations less likely to decompose so that cross slip can be smoothly carried out, thereby improving the plastic toughness of the steel; a small amount of V and Nb can form nano-scale MC to hinder grain boundary migration and thus refine the grains, and the content of impurity elements is controlled by vacuum induction + vacuum consumables / electroslag remelting, and after corresponding heat treatment, the microstructure of the steel is ensured to be lath martensite + film-like austenite + ε-carbide + fine dispersed MC, so that the material has both ultra-high strength and good toughness, and at the same time, the Ni content in the composition is low and does not contain Co, and the cost is reduced by more than 30% compared with A-100 (AerMet100). The mechanical properties of the steel of the present invention are subjected to quasi-static tensile testing in accordance with national standards (GB / T 228.1-2018, GB / T229-2007), and the impact toughness test meets the following requirements: the tensile strength reaches above 1950 MPa, the yield strength reaches above 1500 MPa, the elongation reaches above 10.0%, the area reduction reaches above 40%, and the impact energy reaches above 60 J. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is an optical microscope metallographic photograph of sample 4# in an embodiment of a low-alloy, high-toughness, ultra-high-strength steel according to the present invention. Figure 1 The metallographic structure is magnified 500 times, from which we can see lath martensite + residual austenite + fine spherical carbide, and the original austenite grain size is relatively small. The chemical element composition content in the 4# sample is calculated by wt%, C = 0.24, Si = 1.18, Mn = 1.12, Cr = 0.95, Ni = 2.35, Mo = 1.08, V = 0.11, Nb = 0.028, S ≤ 0.0015, P ≤ 0.005, Fe = balance. The heat treatment process parameters of the 4# sample are as follows: 1050℃ × 1h, oil cooling quenching; 260℃ × 2h, air cooling tempering. The quasi-static mechanical properties of the 4# sample are as follows: tensile strength 1969MPa, yield strength 1683MPa, elongation after fracture 10.0%, cross-sectional shrinkage 45%, and impact energy 64J.
[0015] Figure 2 This is a microstructure morphology picture of sample 4# under a scanning electron microscope in an embodiment of the present invention. Figure 2The magnification of the microstructure is 10,000 times, from which it can be seen that the parallel lath martensite + fine spherical carbides are dispersed in the lath martensite matrix. The chemical element composition content in the 4# sample is calculated by wt%, C = 0.24, Si = 1.18, Mn = 1.12, Cr = 0.95, Ni = 2.35, Mo = 1.08, V = 0.11, Nb = 0.028, S ≤ 0.0015, P ≤ 0.005, Fe = balance. The heat treatment process parameters of the 4# sample are as follows: 1050℃ × 1h, oil cooling quenching; 260℃ × 2h, air cooling tempering. The quasi-static mechanical properties of the 4# sample are as follows: tensile strength 1969MPa, yield strength 1683MPa, elongation after fracture 10.0%, cross-sectional shrinkage 45%, and impact energy 64J. DETAILED DESCRIPTION
[0016] Below is the attached figure ( Figure 1-Figure 2 ) and Examples illustrate the present invention.
[0017] Figure 1 This is an optical microscope metallographic photograph of sample 4# in an embodiment of a low-alloy, high-toughness, ultra-high-strength steel according to the present invention. Figure 2 This is a microstructure morphology picture of the 4# sample under a scanning electron microscope in the embodiment of the present invention. Figure 1 to Figure 2 As shown, a low alloy high toughness ultra-high strength steel includes the following chemical elements and their wt% content: C = 0.22 ~ 0.38, Si = 1.10 ~ 2.20, Mn = 0.80 ~ 2.20, Cr = 0.70 ~ 1.20, Ni = 2.25 ~ 4.50, Mo = 0.50 ~ 1.35, V = 0.09 ~ 0.35, Nb = 0.01 ~ 0.04, S ≤ 0.0015, P ≤ 0.005, Fe = balance. The ultra-high strength and high toughness refer to the following test results according to national standards GB / T228.1-2018 and GB / T229-2007: tensile strength ≥ 1950MPa, yield strength ≥ 1500MPa, elongation ≥ 10.0%, area reduction ≥ 40%, and impact energy ≥ 60J.
[0018] After the low alloy high toughness ultra-high strength steel is subjected to the heat treatment process of quenching + tempering, its metallographic structure can be seen as lath martensite + residual austenite + fine spherical carbide under an optical microscope magnified 500 times, and the original austenite grain size is relatively small. The metallographic structure is as shown in the figure of the specification. Figure 1 After the quenching + tempering heat treatment process, the microstructure of the low alloy high toughness ultra-high strength steel can be seen under a scanning electron microscope magnified 10,000 times that fine spherical carbides are dispersed in the lath martensite matrix. The microstructure is as shown in the attached figure of the specification. Figure 2The quenching + tempering heat treatment process is as follows: 1050°C × 1h + oil cooling quenching, and 260°C × 2h + air cooling tempering. The chemical element composition and wt% content of the low-alloy high-toughness ultra-high strength steel are as follows: C = 0.24, Si = 1.18, Mn = 1.12, Cr = 0.95, Ni = 2.35, Mo = 1.08, V = 0.11, Nb = 0.028, S ≤ 0.0015, P ≤ 0.005, Fe = balance.
[0019] The low alloy high toughness ultra-high strength steel has undergone a smelting process, a forging process, and a post-forging annealing process from front to back before undergoing a quenching + tempering heat treatment process. The smelting process includes smelting in a vacuum induction furnace or smelting in an electric arc furnace + refining outside the furnace, followed by vacuum consumable remelting or electroslag remelting; the forging process is to perform three-stage three-drawing on the smelted steel ingot, specifically including the following steps: Step 1, the initial forging temperature is 1080±10℃, the ingot is roughened to 1 / 2 of the original height, and the ingot is drawn to 4 / 5 of the original height; Step 2, heating to 1080±10℃, roughening to 1 / 2 of the original height, and the ingot is drawn to 4 / 5 of the original height; Step 3, heating to 1080±10℃, roughening to 1 / 2 of the original height, and the ingot is drawn to 4 / 5 of the original height. 10℃, upset to 1 / 2 of the original height, and then forged or rolled into bars or square billets of corresponding sizes according to product requirements. The final forging temperature of the above steps is ≥860℃; the post-forging annealing process includes: heating the forging to 640-660℃ and keeping it for 10h, then furnace cooling to 250-280℃ and keeping it for 10h, then heating to 880℃ and keeping it for ≥12h, air cooling to 250-280℃ and keeping it for 10h, finally heating to 665℃ and keeping it for ≥20h, cooling to 150℃ with the furnace and air cooling out of the furnace.
[0020] The purpose of the present invention is to provide an ultra-high strength steel with low cost and high strength and toughness. The purpose of the present invention is achieved through the following technical scheme: a low-alloy high-toughness ultra-high strength steel of the present invention, the mass percentage of chemical composition: C: 0.22-0.38%, Si: 1.10-2.20%, Mn: 0.80-2.20%, Cr: 0.70-1.20%, Ni: 2.25-4.50%, Mo: 0.50-1.35%, V: 0.09-0.35%, Nb: 0.01-0.04%, S≤0.0015%, P≤0.005%, balance: Fe.
[0021] C: As the main solid solution strengthening element of the steel of the present invention, it strengthens through the solid solution of interstitial atoms after martensite transformation and the precipitation of ε-carbides during low temperature tempering. If the C content is low, the strength is insufficient. When the C content exceeds 0.5%, brittle fracture is likely to occur at the original austenite grain boundary. Taking all factors into consideration, the C content of the present invention is between 0.22% and 0.38%.
[0022] Si: It is added to the steel as a deoxidizer and can also increase the fluidity of the molten steel. In addition, Si can prevent the formation of cementite and improve the tempering resistance of the steel, so that the tempering temperature of the steel of the present invention is lower than the brittle temperature range. However, when the Si content is in the range of 0.8% to 1.0%, the plasticity and toughness of the steel will decrease significantly. Too high Si content will reduce the solubility of the Mo element in the steel matrix, resulting in residual alloy carbides during quenching and heating, which will damage the toughness of the steel. Taking all factors into consideration, the Si content of the present invention is controlled between 1.10 and 2.20%.
[0023] Mn: As an element for removing O and S, Mn is added to steel. It can enhance the deoxidation effect of Si, and Mn can significantly improve the hardenability of the steel of the present invention. The addition of Mn has the comprehensive effects of solid solution strengthening, forming dislocation martensite and film-like residual austenite, and inhibiting network cementite, thereby improving the strength and toughness of the steel. However, too high a Mn content will reduce the Ms point and the strength of the steel. Taking all factors into consideration, the Mn content of the present invention is controlled between 0.80 and 2.20%.
[0024] Cr: Cr is added to the steel to improve the hardenability of the steel of the present invention. The addition of Cr has the combined effects of solid solution strengthening and forming alloy carbides, further improving the strength of the steel. However, a high Cr content forms coarse eutectic carbides, which will reduce the plasticity and toughness of the steel. When the Cr content is within the range of 0.5% to 1.65%, the alloy steel has high strength, high wear resistance, good hardenability and fatigue resistance. Taking all factors into consideration, the Cr content of the present invention is controlled between 0.70% and 1.20%.
[0025] Ni: As an alloying element that expands the γ phase region, it can make screw dislocations less likely to decompose, thereby allowing cross-slip to proceed smoothly, significantly improving the toughness of steel. In addition, Ni can improve the hardenability of steel and reduce the tough-to-brittle transition temperature. However, Ni is a scarce resource in my country, and too high a content not only increases the cost but also reduces the Ms point. Taking all factors into consideration, the Ni content of the present invention is controlled between 2.25% and 4.50%.
[0026] Mo: As a strong carbide-forming element, it can improve the tempering stability of the steel of the present invention. In addition, when Mo exists together with Mn and Cr, it can inhibit or reduce the temper brittleness caused by other elements. When the Mo content is about 0.5%, the temper brittleness of the steel can be basically eliminated, and the second type of temper brittleness of the steel can be effectively prevented. However, Mo is an alloying element that expands the α phase region. Too high a content will reduce the plasticity and toughness of the steel and increase the cost of the steel. Taking all factors into consideration, the Mo content of the present invention is controlled between 0.50 and 1.35%.
[0027] V: As a microalloying element, adding a small amount of V can form MC-type carbides, which hinder the migration of the original austenite grain boundaries during quenching, thereby refining the grains, improving both the strength and plasticity of the steel. However, adding too much V will reduce the toughness. Taking all factors into consideration, the V content of the present invention is controlled between 0.09 and 0.35%.
[0028] Nb: As a microalloying element, adding a small amount of Nb can form nano-scale NbC to hinder grain growth, but Nb and strong carbide elements such as Ti and V are easily combined to form large-sized liquid carbides, which reduce the toughness of steel. Taking all factors into consideration, the Nb content is controlled at 0.01-0.04%.
[0029] The harmful impurity content control requirements of the steel of the present invention are: S≤0.0015%, P≤0.005%.
[0030] The present invention adopts the above-mentioned formula to process a preparation process of low-alloy high-toughness ultra-high strength steel, and the specific processing process is as follows:
[0031] 1) Smelting process: Vacuum induction furnace smelting, electric arc furnace smelting + refining outside the furnace, followed by vacuum consumable remelting or electroslag remelting;
[0032] 2) Forging process: The smelted steel ingot is subjected to a three-upsetting and three-drawing forging process; the specific steps are as follows: Process 1: the initial forging temperature is 1080±10℃, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; Process 2: heating to 1080±10℃, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; Process 3: heating to 1080±10℃, upsetting to 1 / 2 of the original height, and then forging or rolling into bars or square billets of corresponding sizes according to product requirements. The final forging temperature of the above process is ≥860℃.
[0033] 3) Post-forging annealing process: The forgings are heated to 640-660℃ and kept for 10 hours, then furnace cooled to 250-280℃ and kept for 10 hours, then heated to 880℃ and kept for ≥12 hours, air cooled to 250-280℃ and kept for 10 hours, finally heated to 665℃ and kept for ≥20 hours, cooled to 150℃ and air cooled.
[0034] 4) Heat treatment process: The annealed forgings are heated to 950℃~1100℃, kept at this temperature for 1~2h, then oil quenched to room temperature, then heated to 200℃~300℃, kept at this temperature for 2~3h, and taken out and air-cooled to room temperature.
[0035] Embodiment: No. 1 and No. 2 test steels were smelted by vacuum induction + electroslag remelting, and No. 3 and No. 4 test steels were smelted by vacuum induction + vacuum consumable smelting, and the chemical compositions are shown in Table 1. The smelted steel ingots were subjected to a three-upsetting and three-drawing forging process; the specific steps are as follows: process 1: the initial forging temperature is 1080°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; process 2: heating to 1080°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; process 3: heating to 1080°C, upsetting to 1 / 2 of the original height, and finally fine forging into a round ingot with a diameter of 390 mm and a length of 3100 mm. The final forging temperature of the above process is ≥860°C. The forgings are heated to 640-660℃ and kept for 10h, then furnace cooled to 250-280℃ and kept for 10h, then heated to 880℃ and kept for ≥12h, air cooled to 250-280℃ and kept for 10h, finally heated to 665℃ and kept for ≥20h, cooled to 150℃ with the furnace, air cooled, and then heat treated using the heat treatment system in Table 2.
[0036] Table 1 Chemical composition of the embodiments of the present invention (wt, %)
[0037] serial number C Si Mn Cr Ni Mo V Nb Co 1# 0.38 2.20 2.10 1.10 3.95 1.15 0.28 0.033 — 2# 0.28 2.10 1.98 1.04 2.85 0.95 0.24 0.012 — 3# 0.34 1.10 0.85 0.75 2.26 0.65 0.34 0.031 — 4# 0.24 1.18 1.12 0.95 2.35 1.08 0.11 0.028 — Comparative Example 1 0.23 — — 2.91 11.59 1.20 — — 13.60
[0038] Table 2 Heat treatment process parameters
[0039] serial number Quenching Cold treatment Tempering 1# 960℃×1h, oil cooling — 220℃×2h, air cooling 2# 960℃×1h, oil cooling — 300℃×2h, air cooling 3# 960℃×1h, oil cooling — 260℃×2h, air cooling 4# 1050℃×1h, oil cooling — 260℃×2h, air cooling Comparative Example 1 885℃×1h, oil cooling -73℃×1h, air cooling 482℃×5h, air cooling
[0040] Table 3 Quasi-static mechanical properties
[0041] serial number Tensile strength / MPa Yield strength / MPa Elongation after break / % Sectional shrinkage / % Impact energy / J 1# 2024 1605 12.5 47 67 2# 1950 1602 10.0 48 66 3# 2020 1625 12.5 52 66 4# 1969 1683 10.0 45 64 Comparative Example 1 1940 1726 11.5 59 76
[0042] Table 3 shows the quasi-static mechanical properties of Example 1-4# steel. Compared with Comparative Example 1 (AerMet100), the overall mechanical properties are equivalent to A-100 (AerMet100), but the composition does not contain Co and the Ni content is low, and the cost is reduced by more than 30%.
[0043] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. It is pointed out here that the above description helps those skilled in the art to understand the invention, but does not limit the protection scope of the invention. Any equivalent replacement, modification and / or simplification of the above description without departing from the essence of the invention falls within the protection scope of the invention.
Claims
1. A low alloy high toughness ultra-high strength steel, characterized in that: The invention comprises the following chemical elements and their wt% contents: C=0.22-0.38, Si=1.10-2.20, Mn=0.80-2.20, Cr=0.70-1.20, Ni=2.25-4.50, Mo=0.50-1.35, V=0.09-0.35, Nb=0.01-0.04, S≤0.0015, P≤0.005, Fe=balance; The ultra-high strength and high toughness refer to the following test results according to the national standards GB / T 228.1-2018 and GB / T229-2007: tensile strength ≥1950MPa, yield strength ≥1500MPa, elongation ≥10.0%, area reduction ≥40%, and impact energy ≥60J; After the low-alloy high-toughness ultra-high-strength steel has been subjected to a heat treatment process of quenching and tempering, its metallographic structure can be seen as lath martensite + residual austenite + fine spherical carbides under an optical microscope magnified 500 times; After the low-alloy high-toughness ultra-high-strength steel has been subjected to a quenching + tempering heat treatment process, its microstructure can be seen to have fine spherical carbides dispersed in a lath martensite matrix under a scanning electron microscope magnification of 10,000 times.
2. The low alloy high toughness ultra-high strength steel according to claim 1, characterized in that: The quenching + tempering heat treatment process is as follows: 1050°C × 1h + oil-cooling quenching, and 260°C × 2h + air-cooling tempering. The chemical element composition and wt% content of the low-alloy high-toughness ultra-high strength steel are as follows: C = 0.24, Si = 1.18, Mn = 1.12, Cr = 0.95, Ni = 2.35, Mo = 1.08, V = 0.11, Nb = 0.028, S ≤ 0.0015, P ≤ 0.005, Fe = balance.
3. The low alloy high toughness ultra-high strength steel according to claim 1, characterized in that: The low alloy high toughness ultra-high strength steel undergoes a smelting process, a forging process, and a post-forging annealing process in sequence from front to back before undergoing a quenching+tempering heat treatment process.
4. The low alloy high toughness ultra-high strength steel according to claim 3, characterized in that: The smelting process includes smelting in a vacuum induction furnace or smelting in an electric arc furnace + refining outside the furnace, followed by vacuum consumable remelting or electroslag remelting; the forging process is to perform three-upsetting and three-drawing on the smelted steel ingot, specifically including the following steps: step 1, the initial forging temperature is 1080±10°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; step 2, heating to 1080±10°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height; step 3, heating to 1080±10°C, upsetting to 1 / 2 of the original height, and drawing to 4 / 5 of the original height. 10℃, upset to 1 / 2 of the original height, and then forged or rolled into bars or square billets of corresponding sizes according to product requirements. The final forging temperature of the above steps is ≥860℃; the post-forging annealing process includes: heating the forging to 640-660℃ and keeping it for 10h, then furnace cooling to 250-280℃ and keeping it for 10h, then heating to 880℃ and keeping it for ≥12h, air cooling to 250-280℃ and keeping it for 10h, finally heating to 665℃ and keeping it for ≥20h, cooling to 150℃ with the furnace and air cooling out of the furnace.
Citation Information
Patent Citations
High-toughness ultrahigh-strength D506A steel easy for rotary extrusion and easy to weld and preparation method thereof
CN104328359A
High-plasticity-toughness low-alloy ultrahigh-strength steel and preparation method
CN111979487A
High-toughness ultrahigh-strength steel and manufacturing method thereof
CN114107821A